ChemInform Abstract: Addressing the Configuration Stability of Lithiated Secondary Benzylic Carbamates for the Development of a Noncryogenic Stereospecific Boronate Rearrangement. Issue 10 (March 2015) - Fandrick, Keith R.; et al., et al.
Abstract A new noncryogenic process using LDA instead of BuLi combined with an in situ trapping of the unstable lithiated carbamate is developed for the Aggerwal stereospecific boronate rearrangement of benzylic carbamates.